Sang Kancil and the tiger - Carrington, Jim (Cambridge : Cambridge University Press, 2016)
Tiger wants to eat Sang Kancil. Can Sang Kancil trick Tiger? At Turquoise Band descriptions of places and people are extended with literary phrases and expressions which provide new challenges. Vocabulary is often less common and requires the reader to use their knowledge of spelling patterns. Contains full teaching support including learning outcomes, curriculum links and follow-up activities.
Keywords: Children's - stories; English - fiction